Effects of permafrost thawing on vegetation and soil carbon pool losses on the Qinghai-Tibet Plateau, China - Wang Genxu; Li Yuanshou; Wang Yibo; Wu Qingbo (Geoderma, 2008)
Bearing a total organic carbon (TOC) content of 9.3-10.7 kg c/m(2), alpine grassland soils of the Qinghai-Tibet plateau's permafrost region bear a greater organic carbon pool than do grassland soils in other regions of China or than tropical savannah soils. The easily released light fraction organic carbon (LFOC) accounts for 34-54% of the TOC and is particularly enriched in the topsoil (0-0.10 in). The LFOC in the organic carbon pool of alpine cold meadow and alpine cold steppe soils decreased at exponential and quadratic rates, respectively, as the vegetative cover decreased. When the vegetative cover of alpine cold meadows decreased from > 80 dm(2)/m(2) to 60 dm(2)/m(2), the topsoil TOC and LFOC dropped by 20.4% and 38.4%, respectively. Similarly, when the vegetative cover of alpine cold meadow decreased from 50 dm(2)/m(2) to 30 dm(2)/m(2) and < 15 dm(2)/m(2), the topsoil LFOC content dropped by 60% and 86.7%, respectively. Under climatic warming, the degradation of permafrost and vegetation have resulted in serious soil organic carbon (SOC) loss from the carbon pool. Land cover changes that occurred between 1986 and 2000 are estimated to have resulted in a 1.8 Gg C (120 Mg C/yr) loss in SOC, and a concomitant 65% decrease in the LFOC, in the 0-0.30 in soil layer in the Qinghai-Tibet plateau's permafrost regions. Since the region's ecosystems are quite sensitive to global climate changes, if global warming persists, alpine cold grassland ecosystems are expected to further degrade. Hence, the influence of global climatic change on soil carbon emissions from alpine grasslands should receive more attention. (C) 2007 Elsevier B.V. All rights reserved.